PERAN ORANG TUA DALAM MENDUKUNG KEGIATAN PEMBELAJARAN ANAK SMP DI RUMAH PADA MASA PANDEMI COVID-19 DI DESA KUMPULREJO KECAMATAN PARENGAN KABUPATEN TUBAN TAHUN PELAJARAN 2020/2021 - Ninik Hidayati; Ika Wulandari (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
Education outside the family, does not mean relinquishing the responsibility of parents in the world of education, this is done by parents due to the limited knowledge possessed by parents. But there are things that become cloudy in the process of children's learning activities carried out online. Based on the background of the problem, this researcher is expected to provide answers to the formulation of the problem described: 1) What is the role of parents in supporting the learning activities of junior high school children at home during the covid-19 pandemic in Kumpulrejo Village, Parengan District, Tuban Regency. 2) What are the inhibiting and supporting factors for junior high school children's learning activities at home during the COVID-19 pandemic in Kumpulrejo Village, Parengan District, Tuban Regency. The purpose of this study was 1) To determine the role of parents in supporting learning activities for junior high school children at home during the COVID-19 pandemic in Kumpulrejo Village, Parengan District, Tuban Regency. 2) to find out the inhibiting and supporting factors for junior high school children's learning activities at home during the covid-19 pandemic in Kumpulrejo Village, Parengan District, Tuban Regency This study used a qualitative descriptive research method which took place in the village of Kumpulrejo. The process of collecting research data using the methods of observation, interviews and documentation. The data analysis technique used is data reduction, data display, conclusion drawing or data verification (conclusion drawing/verification). The results of this study can be concluded that the role of parents in supporting the learning activities of junior high school children at home during the COVID-19 pandemic in Kumpulrejo Village, Parengan District, Tuban Regency is very important for their children. Children will be more enthusiastic about online learning which is done at home with the role of parents providing motivation and enthusiasm for children, parents as facilitators, parents supervising children in learning. The role of parents in the learning process at home has been carried out well. Although there were obstacles with the existence of civid-19 this research also went smoothly.